Phytochemical Screening and In vitro Evaluation of Reducing Power Cytotoxicity and Anti Fungal Activities of Ethanol Extracts of Cucumis sativus - Mallik, Jony (International Journal of Pharmaceutical & Biological Archive, 2012)
Phytochemical Screening and In vitro Evaluation of Reducing Power Cytotoxicity and Anti Fungal Activities of Ethanol Extracts of Cucumis sativus